Low-defect few-layer graphene water-based conductive paste and preparation method and application thereof
By combining low-defect oligolayer graphene and amphiphilic polythiophene conductive additives, the problems of graphene sheet stacking and dispersant are solved, and a graphene water-based conductive slurry with high dispersion stability and excellent conductive properties is achieved, which is suitable for applications such as batteries, conductive coatings, conductive inks and flexible sensors.
Patent Information
- Application Number
- CN202511208551.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-27
AI Technical Summary
Existing graphene preparation methods lead to sheet stacking and structural defects, which affect the conductive properties. The use of dispersants also brings stability and electrode contact problems, making it difficult to achieve low defects, good dispersibility and excellent conductivity at the same time.
Low-defect oligolayer graphene and amphiphilic polythiophene conductive additives are used to prepare graphene through room-temperature intercalation, chemical expansion and aqueous phase exfoliation. The branched amphiphilic polythiophene is combined to improve the dispersion and conductive network continuity.
The high dispersion stability and excellent conductive properties of low-defect few-layer graphene are achieved, making it suitable for applications such as batteries, conductive coatings, conductive inks and flexible sensors.
Abstract
Description
Technical Field
[0001] The invention relates to a low-defect few-layer graphene aqueous conductive slurry and a preparation method and application thereof. Background Art
[0002] With the rapid development of the new energy industry, the demand for high-performance conductive materials is growing. Graphene, a two-dimensional material with excellent conductivity, high specific surface area, and good mechanical properties, shows broad application prospects in batteries, supercapacitors, and conductive coatings. Few-layer graphene (≤5 layers) is considered an ideal conductive carrier due to its low electron transport resistance and high structural integrity.
[0003] However, traditional graphene preparation methods present numerous limitations that limit their performance. For example, the widely used Hummers method, which involves preparing graphene oxide (GO) and then reducing it to graphene at high temperatures, can easily lead to stacking between the sheets and the creation of numerous structural defects during the reduction process, significantly impacting the conductivity of the final material. Furthermore, residual oxygen-containing functional groups from incomplete reduction can further reduce graphene's conductivity.
[0004] In aqueous systems, graphene is prone to aggregation due to its strong van der Waals forces and π-π interactions, so dispersants are often added to improve its dispersion stability. However, the use of dispersants also brings a series of problems. For example, excessive dispersants will adsorb on the graphene surface, occupy active sites, hinder direct contact between it and the electrode material, and thus weaken the construction of the conductive network. Some dispersant residues in the battery system may lead to increased internal resistance, affecting high-current charge and discharge performance, and limiting its application in high-power devices.
[0005] Furthermore, current mainstream graphene production processes face an irreconcilable conflict between controlling the number of graphene layers and maintaining lattice integrity. While mechanical exfoliation methods (such as ultrasonic exfoliation or sanding) can reduce the number of graphene layers to a certain extent, further reduction to a few layers (≤5) is extremely time-consuming and inefficient. While chemical reduction methods offer some advantages in controlling the number of layers, damage to the sp² hybrid structure of graphene oxide during reduction is still unavoidable. For example, while high-temperature thermal reduction (>800°C) can help remove oxygen-containing groups and restore the sp² structure, this process is often accompanied by problems such as sheet curling and hole formation.
[0006] In summary, developing a water-based conductive slurry of few-layer graphene that can combine low defect density, good dispersibility and excellent conductive properties is the key to promoting its widespread application in high-performance electrochemical energy storage and other conductive materials. Summary of the Invention
[0007] The purpose of the present invention is to provide a low-defect few-layer graphene aqueous conductive slurry and its preparation method and application, so as to solve the technical problems mentioned in the above background technology.
[0008] The technical solution for achieving the purpose of the present invention is:
[0009] In a first aspect, the present invention provides a low-defect few-layer graphene aqueous conductive slurry, wherein the raw material components include 1 to 3 parts by mass of low-defect few-layer graphene, 100 parts by mass of ultrapure water, and 0.8 to 1.2 parts by mass of a conductive additive.
[0010] Furthermore, the low-defect few-layer graphene is obtained by first intercalating graphite powder at room temperature, then chemically expanding it, and then exfoliating it using an aqueous solution of 2',3'-dideoxyadenosine 5'-triphosphate.
[0011] Furthermore, the conductive additive is amphiphilic polythiophene.
[0012] Furthermore, the amphiphilic polythiophene is obtained by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 3-[10-(4-methylphenyl ether)decyl)]thiophene, and 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine as polymerization monomers and then treating with hydrogen bromide and anhydrous acetic anhydride.
[0013] In a second aspect, the present invention provides a method for preparing the low-defect, few-layer graphene aqueous conductive slurry as described in the first aspect, comprising the following preparation steps:
[0014] (1) Weigh each raw material component according to its mass fraction;
[0015] (2) Under argon protection, the low-defect few-layer graphene weighed in step (1) is dispersed in anhydrous dimethyl sulfoxide 4 to 6 times its mass and ultrasonically dispersed for 55 to 65 minutes, and then a conductive additive is added, and ultrasonic dispersion is continued for 25 to 35 minutes. Then, the temperature is first raised to 58 to 62°C, and after cooling to room temperature, it is stirred at 600 to 800 rpm for 23 to 25 hours, and sodium hydride is added three times, with an interval of 15 to 25 minutes between each two times, and the amount added each time is 0.32 to 0.48 parts by mass. Then, the temperature is raised to 70 to 80°C, stirred and refluxed for 5.5 to 6.5 hours, and then 18 to 20 parts by mass of ethyl acetate is added to quench, and then 27 to 30 parts by mass of ethyl acetate is added. Then, the mixture is filtered, washed with dichloromethane and ether for 2 to 4 times respectively, and then dried in a vacuum oven at 50°C to constant weight to obtain a low-defect few-layer graphene composite conductive material;
[0016] (3) The low-defect few-layer graphene composite conductive material obtained in step (2) is mixed with the ultrapure water weighed in step (1), and ultrasonically dispersed for 55 to 65 minutes to obtain a low-defect few-layer graphene aqueous conductive slurry.
[0017] Furthermore, the preparation steps of the low-defect few-layer graphene are as follows:
[0018] A1. Graphite powder and chromium trioxide were mixed in a mass ratio of 1:8-9. 6-8 parts by mass of 36-38% hydrochloric acid were then added. The mixture was stirred at 1000-1400 rpm for 110-130 minutes under sealed conditions. The filtrate was then filtered and washed repeatedly with deionized water and acetone until the pH was neutral. The filtrate was then vacuum-dried at 60°C to constant weight to obtain room-temperature intercalated graphite powder.
[0019] A2. Immerse 0.2 parts by weight of room-temperature intercalated graphite powder in 38-42 parts by weight of a 30% hydrogen peroxide solution. Allow to react for 23-25 hours, then filter and wash repeatedly with deionized water and acetone until the filtrate reaches a neutral pH. Dried under vacuum at 60°C to constant weight to obtain a graphene precursor.
[0020] A3. Dissolve 0.015–0.025 parts by weight of 2',3'-dideoxyadenosine 5'-triphosphate sodium salt in 20 parts by weight of deionized water. Add 0.02 parts by weight of a graphene precursor and perform ultrasonic exfoliation at 100 W for 55–65 minutes at 10–15°C. Centrifuge the mixture at 5000 rpm for 25–35 minutes, collect the supernatant, filter, and dry to obtain low-defect, oligolayer graphene.
[0021] Furthermore, 78% of the low-defect few-layer graphene has a thickness of less than 2 nm, and 74% of the low-defect few-layer graphene has a sheet diameter of 1 to 6 μm.
[0022] Furthermore, the ratio of the D peak to the G peak of the low-defect few-layer graphene is not higher than 0.2.
[0023] Furthermore, the preparation method of the amphiphilic polythiophene is as follows:
[0024] Under nitrogen protection, 0.51-0.53 parts by mass of 3-[10-(4-methylphenyl ether)decyl)]thiophene and 0.23-0.24 parts by mass of 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine were mixed, 6.3-7 parts by mass of dry tetrahydrofuran were added, and the mixture was stirred for 10-20 minutes. Subsequently, 0.194-0.196 parts by mass of isopropylmagnesium chloride was added dropwise at a rate of 1-3 seconds per drop under ice bath conditions, and the mixture was reacted at room temperature in the dark for 25-35 minutes to obtain a formatted monomer A. Under nitrogen protection and ice bath conditions, 0. To 776~0.778 parts by mass of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 0.194~0.196 parts by mass of isopropyl magnesium chloride was added dropwise at a rate of 1~3s / drop, and the mixture was allowed to react at room temperature in the dark for 25~35min to obtain the formatted monomer B; under nitrogen protection, 0.0097~0.0099 parts by mass of 1,3-bis(diphenylphosphinopropane) nickel dichloride and 2.25 parts by mass of tetrahydrofuran were mixed and stirred for 25~35min, and then the formatted monomer A was added dropwise at a rate of 1~3s / drop in an ice bath. After the addition was complete, the ice bath was removed. The reaction was stirred at room temperature for 2.5 to 3.5 hours, the formatted monomer B was added, and the reaction was continued to be stirred at room temperature for 2.5 to 3.5 hours. After the reaction was completed, it was quenched with 1M hydrochloric acid under ice bath conditions, and then deionized water and the extracted product were used until the aqueous phase was almost colorless. The organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure on a rotary evaporator. Then 10 parts by mass of chloroform was added to dissolve it and added to n-hexane in batches for precipitation. The mixture was centrifuged at 5800 rpm for 2 to 3 times, each time for 10 minutes, to remove oligomers with small molecular weight and unreacted monomers, and the upper unreacted phase was discarded. The mixture was dried in a vacuum oven at 45°C for 7.5-8.5h, and then mixed with 20.1-20.3 parts by mass of 48% hydrobromic acid and 20.1-20.3 parts by mass of acetic anhydride under nitrogen protection, and then heated to 99-101°C. After reacting for 20-25h, the organic phase was extracted 2-4 times with deionized water and ether, and washed with saturated sodium bicarbonate solution until the organic phase was neutral. The organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure in a rotary evaporator. The amphiphilic polythiophene was obtained by vacuum drying at 45°C in a vacuum oven for 7.5-8.5h.
[0025] In a third aspect, the present invention provides an application of the low-defect few-layer graphene aqueous conductive paste as described in the first aspect, and the application of the low-defect few-layer graphene aqueous conductive paste in the preparation of batteries, conductive coatings, conductive inks, flexible sensors, and electric heating films.
[0026] By adopting the above technical solution, the present invention has the following beneficial effects:
[0027] (1) The low-defect few-layer graphene aqueous conductive paste of the present invention comprises low-defect few-layer graphene, ultrapure water, and a conductive additive. The conductive properties of the low-defect few-layer graphene aqueous conductive paste are improved by using low-defect few-layer graphene and adding a conductive additive.
[0028] (2) The low-defect few-layer graphene of the present invention is prepared by first intercalating graphite with chromium trioxide and concentrated hydrochloric acid at room temperature, and then immersing it in hydrogen peroxide for chemical expansion. Hydrogen peroxide decomposes under the catalytic action of chromium ions to release oxygen, causing the graphite to stretch along the axial height to form a fluffy and porous worm-like structure. Then, 78% of the graphene obtained by aqueous phase exfoliation with an aqueous solution of 2',3'-dideoxyadenosine 5'-triphosphate has a thickness of less than 2nm, and the ratio of the D peak to the G peak is not higher than 0.15, showing a small number of layers and low defects. The graphene obtained by aqueous phase exfoliation with an aqueous solution of 2',3'-dideoxyadenosine 5'-triphosphate has good dispersibility, and there is no obvious sedimentation after standing for two months, the concentration decreases slowly, and the dispersion stability is good.
[0029] (3) The conductive additive of the low-defect oligolayer graphene aqueous conductive paste of the present invention is an amphiphilic polythiophene with a branched structure having 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine as the branching center and a polymer of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene and 3-[10-(4-methylphenyl ether)decyl]thiophene as the branched chain, which is prepared by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 3-[10-(4-methylphenyl ether)decyl]thiophene and 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine and then treating the polymer with hydrogen bromide and anhydrous acetic anhydride. In addition, hydrophilic branched triethylene glycol and hydrophobic branched bromodecane are introduced into the amphiphilic polythiophene with a branched structure to give the conductive additive amphiphilicity and improve the dispersibility of the conductive additive in ultrapure water.
[0030] The preparation mechanism of amphiphilic polythiophene is as follows:
[0031] .
[0032] (4) Low-defect few-layer graphene aqueous conductive slurry: Low-defect few-layer graphene and conductive additives are pre-mixed and then dispersed in ultrapure water to obtain low-defect few-layer graphene aqueous conductive slurry, wherein the low-defect few-layer graphene is dispersed in the amphiphilic polythiophene through the cavity of the branched amphiphilic polythiophene, so that the amphiphilic polythiophene and the low-defect few-layer graphene are evenly dispersed, and the imidazole on the 2',3'-dideoxyadenosine 5'-triphosphate on the surface of the low-defect few-layer graphene reacts with the bromodecane side chain on the conductive additive to form an imidazolium salt, which further enhances the dispersibility of the low-defect few-layer graphene and the conductive additive in ultrapure water, while forming a continuous conductive network with the low-defect few-layer graphene, thereby enhancing the conductive properties of the low-defect few-layer graphene aqueous conductive slurry. DETAILED DESCRIPTION
[0033] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0034] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0035] The following examples are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.
[0036] The raw materials of the embodiments and comparative examples are as follows:
[0037] Graphite powder with a mesh size of 80-120 and a purity of 99.95% was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0038] 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene: Under nitrogen protection, 3 parts by mass of (2,5-dibromothiophen-3-yl) methanol was mixed with 100 parts by mass of dry dichloromethane, stirred for 20 minutes under ice-water bath conditions to maintain the reaction temperature at about 0°C, and 4.98 parts by mass of phosphorus tribromide was added dropwise at 2s / drop while stirring at 1200 rpm. After stirring at room temperature for 5 hours, 20 parts by mass of 10% sodium bicarbonate solution was added dropwise at 2s / drop to quench the reaction, and the phosphorus tribromide that was not reacted was converted into a water-soluble salt. Then, the mixture was passed through a diatomaceous earth column to remove impurities such as bromine, and then 50 mL of dichloromethane was added to separate the liquids. The organic phase was washed twice with distilled water, anhydrous magnesium sulfate powder was added and stirred continuously to remove water in the organic phase, and then the solid matter was removed by suction to obtain a dry organic phase, and the solvent was removed by rotary evaporation to obtain 2,5-dibromo-3-methylbromothiophene;
[0039] Under nitrogen protection, 3 parts by mass of triethylene glycol monomethyl ether was dissolved in 72 parts by mass of tetrahydrofuran solvent, and 0.5 parts by mass of sodium hydride powder was added while stirring. A large amount of bubbles were observed. After the addition was completed, the reaction bottle was covered with an oil seal and reacted at room temperature for 1 hour. When no bubbles were generated in the solution, the oil seal was removed in time, the temperature was raised to 80°C, and 3 parts by mass of 2,5-dibromo-3-methylbromothiophene was dissolved in 22.5 parts by mass of tetrahydrofuran. The solution was added dropwise for about 10 minutes. After the reaction for 5 hours, the organic phase was repeatedly extracted three times with ether to obtain the organic phase, and then the organic phase was washed twice with distilled water. After taking the organic phase, anhydrous magnesium sulfate was added to remove water, and the solid matter was removed by suction filtration. The solvent was then distilled off under reduced pressure and purified by column chromatography. The single eluent was a mixed solvent of n-hexane: ethyl acetate with a volume ratio of = 7:3. The purified solution was subjected to rotary evaporation to remove the solvent to obtain 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene;
[0040] The detailed preparation mechanism is as follows:
[0041] .
[0042] Preparation steps of 3-[10-(4-methylphenyl ether)decyl]thiophene: 0.616 parts by mass of potassium hydroxide (0.616 g, 11 mmol) and 1.25 parts by mass of p-methoxyphenol are dissolved in 13.6 parts by mass of methanol to obtain a mixed solution A; 7.5 parts by mass of 1,10-dibromodecane are dissolved in 13.6 parts by mass of 56°C acetone, and then the mixed solution A is added dropwise to a flask for 1 hour. After refluxing for 30 hours, the mixture is separated using a pressure reducing device, and the separated residue is washed and filtered with 330 parts by mass of boiling hexane. After the solid is filtered out, it is washed again with an equal amount of boiling hexane. After filtration, the obtained solid is passed through a chromatographic column (silica gel, hexane / dichloromethane volume ratio = 1 / 1) to obtain intermediate product 1;
[0043] 1.6 parts by mass of intermediate product 1 was dissolved in 28.56 parts by mass of dry ether to obtain an ether solution of intermediate product 1; under argon, 0.224 parts by mass of magnesium powder and 11 parts by mass of dry ether were refluxed and mixed, and then the ether solution of intermediate product 1 was added dropwise over 3 hours to obtain a mixed solution B; 0.026 parts by mass of 1,3-bis(diphenylphosphinopropane)nickel dichloride and 0.84 parts by mass of 3-bromothiophene were dissolved in 15 parts by mass of argon. The mixture was added to a portion of dry ether, placed in a second three-necked flask, heated, and refluxed under argon protection, followed by the addition of mixed solution B. After continuing to heat and reflux for 19 hours, it was hydrolyzed with cold 0.2M hydrochloric acid and extracted with dichloromethane. The organic phase was washed with water until the solution became neutral and dried over magnesium sulfate. The ether was removed using a vacuum device and purified by silica gel chromatography (silica gel, n-hexane / ether volume ratio = 15 / 1) to obtain 3-[10-(4-methylphenyl ether)decyl]thiophene;
[0044] The detailed preparation mechanism is as follows:
[0045] .
[0046] (Example 1)
[0047] A method for preparing a low-defect, few-layer graphene aqueous conductive slurry comprises the following steps:
[0048] (1) Weigh the raw material components according to the following mass parts: 1 mass part of low-defect few-layer graphene, 100 mass parts of ultrapure water, and 1.2 mass parts of conductive additive;
[0049] (2) Under argon protection, the low-defect few-layer graphene weighed in step (1) was dispersed in anhydrous dimethyl sulfoxide (DMSO) 4 times its mass and ultrasonically dispersed for 55 minutes, and then a conductive additive was added and ultrasonic dispersion was continued for 25 minutes. Then, the temperature was first raised to 58°C, cooled to room temperature, and stirred at 600 rpm for 23 hours. Then, sodium hydride was added three times with an interval of 15 minutes between each two times, and the amount added each time was 0.32 parts by mass. Then, the temperature was raised to 70°C, stirred and refluxed for 5.5 hours, and then 18 parts by mass of ethyl acetate was added to quench, and then 27 parts by mass of ethyl acetate was added. Then, the mixture was filtered, washed twice with dichloromethane and ether respectively, and then dried in a vacuum oven at 50°C to constant weight to obtain a low-defect few-layer graphene composite conductive material.
[0050] (3) The low-defect few-layer graphene composite conductive material obtained in step (2) is mixed with the ultrapure water weighed in step (1), and ultrasonically dispersed for 55 minutes to obtain a low-defect few-layer graphene aqueous conductive slurry.
[0051] The preparation steps of the low-defect few-layer graphene are as follows:
[0052] A1. Graphite powder and chromium trioxide were mixed in a mass ratio of 1:8. Six parts by mass of 36% hydrochloric acid were then added. The mixture was stirred at 1000 rpm under sealed conditions for 110 minutes. The mixture was then filtered and washed repeatedly with deionized water and acetone until the filtrate reached a neutral pH. The mixture was then vacuum-dried at 60°C to a constant weight to obtain room-temperature intercalated graphite powder.
[0053] A2. 0.2 parts by weight of room temperature intercalated graphite powder was immersed in 38 parts by weight of a 30% hydrogen peroxide solution. After reacting for 23 hours, the mixture was filtered and then repeatedly filtered and washed with deionized water and acetone until the filtrate had a neutral pH. The filtrate was then vacuum dried at 60°C to a constant weight to obtain a graphene precursor.
[0054] A3. Dissolve 0.015 parts by mass of 2',3'-dideoxyadenosine 5'-triphosphate sodium salt in 20 parts by mass of deionized water by stirring. Then, add 0.02 parts by mass of a graphene precursor. Ultrasonic exfoliation is performed at 100 W at 10°C for 55 minutes. The mixture after ultrasonic exfoliation is centrifuged at 5000 rpm for 25 minutes, and the supernatant is collected, filtered, and dried to obtain low-defect, oligolayer graphene.
[0055] 78% of the low-defect few-layer graphene has a thickness of 2.5nm, and 71% of the low-defect few-layer graphene has a sheet diameter of 1~6μm.
[0056] The ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.18.
[0057] The preparation method of the amphiphilic polythiophene is as follows:
[0058] Under nitrogen protection, 0.51 parts by mass of 3-[10-(4-methylphenyl ether)decyl)]thiophene and 0.23 parts by mass of 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine were mixed, 6.3 parts by mass of dry tetrahydrofuran were added, and stirred for 10 minutes. Subsequently, 0.194 parts by mass of isopropylmagnesium chloride was added dropwise at a rate of 1s / drop under ice bath conditions, and the reaction was carried out at room temperature in the dark for 25 minutes to obtain a formatted monomer A; under nitrogen protection and ice bath conditions, 0.776 To 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 0.194 parts by mass of isopropyl magnesium chloride was added at 1s / drop, and the mixture was reacted at room temperature in the dark for 25 minutes to obtain a formatted monomer B; under nitrogen protection, 0.0097 parts by mass of 1,3-bis(diphenylphosphinopropane) nickel dichloride and 2.25 parts by mass of tetrahydrofuran were mixed and stirred for 25 minutes, and then the formatted monomer A was added at 1s / drop under ice bath conditions. After the addition was complete, the ice bath was removed and the reaction was stirred at room temperature for 2 minutes. .5h, add the formatted monomer B, continue to stir and react at room temperature for 2.5h, quench with 1M hydrochloric acid under ice bath conditions after the reaction, then use deionized water and extract the product until the aqueous phase is almost colorless, collect the organic phase, add anhydrous magnesium sulfate to dry, filter, and remove the solvent under reduced pressure on a rotary evaporator, then add 10 parts by mass of chloroform to dissolve and add it in n-hexane to precipitate, centrifuge twice at 5800 rpm, each centrifugation for 10 minutes to remove small molecular weight oligomers and unreacted monomers, pour The upper layer of poor solvent was removed, and the mixture was vacuum dried in a vacuum oven at 45°C for 7.5 hours. Subsequently, the mixture was mixed with 20.1 parts by mass of 48% hydrobromic acid and 20.1 parts by mass of acetic anhydride under nitrogen protection, and then the temperature was raised to 99°C. After reacting for 20 hours, the organic phase was extracted twice with deionized water and ether, and the organic phase was washed with saturated sodium bicarbonate solution until the organic phase was neutral. The organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure in a rotary evaporator. The mixture was vacuum dried in a vacuum oven at 45°C for 7.5 hours to obtain amphiphilic polythiophene.
[0059] (Example 2)
[0060] A method for preparing a low-defect, few-layer graphene aqueous conductive slurry comprises the following steps:
[0061] (1) Weigh the raw material components according to the following mass parts: 3 parts by mass of low-defect few-layer graphene, 100 parts by mass of ultrapure water, and 1 part by mass of conductive additive;
[0062] (2) Under argon protection, the low-defect few-layer graphene weighed in step (1) was dispersed in anhydrous dimethyl sulfoxide 5 times its mass and ultrasonically dispersed for 60 minutes, and then a conductive additive was added and ultrasonic dispersion was continued for 30 minutes. Then, the temperature was first raised to 60°C, cooled to room temperature, and stirred at 700 rpm for 24 hours. Then, sodium hydride was added three times with an interval of 20 minutes between each two times, and the amount added each time was 0.4 parts by mass. Then, the temperature was raised to 75°C, stirred and refluxed for 6 hours, and then 19 parts by mass of ethyl acetate was added to quench, and then 28.5 parts by mass of ethyl acetate was added. Then, the mixture was filtered, washed with dichloromethane and ether for 3 times respectively, and then dried in a vacuum oven at 50°C to constant weight to obtain a low-defect few-layer graphene composite conductive material;
[0063] (3) The low-defect few-layer graphene composite conductive material obtained in step (2) is mixed with the ultrapure water weighed in step (1), and ultrasonically dispersed for 60 minutes to obtain a low-defect few-layer graphene aqueous conductive slurry.
[0064] The preparation steps of the low-defect few-layer graphene are as follows:
[0065] A1. Graphite powder and chromium trioxide were mixed in a mass ratio of 1:8.5. 7 parts by mass of 36% hydrochloric acid were then added. The mixture was stirred at 1200 rpm under sealed conditions for 120 minutes. The mixture was then filtered and washed repeatedly with deionized water and acetone until the filtrate reached a neutral pH. The mixture was then vacuum-dried at 60°C to a constant weight to obtain room-temperature intercalated graphite powder.
[0066] A2. 0.2 parts by weight of room temperature intercalated graphite powder was immersed in 40 parts by weight of a 30% hydrogen peroxide solution. After reacting for 24 hours, the mixture was filtered and then repeatedly filtered and washed with deionized water and acetone until the filtrate had a neutral pH. The filtrate was then vacuum dried at 60°C to a constant weight to obtain a graphene precursor.
[0067] A3. Dissolve 0.020 parts by mass of 2',3'-dideoxyadenosine 5'-triphosphate sodium salt in 20 parts by mass of deionized water by stirring. Then, add 0.02 parts by mass of a graphene precursor. Ultrasonic exfoliation is performed at 100 W for 60 minutes at 13°C. The mixture after ultrasonic exfoliation is centrifuged at 5000 rpm for 30 minutes, and the supernatant is collected, filtered, and dried to obtain low-defect, oligolayer graphene.
[0068] 78% of the low-defect few-layer graphene has a thickness of less than 1 nm, and 74% of the low-defect few-layer graphene has a sheet diameter of 1 to 6 μm.
[0069] The ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.16.
[0070] The preparation method of the amphiphilic polythiophene is as follows:
[0071] Under nitrogen protection, 0.52 parts by mass of 3-[10-(4-methylphenyl ether)decyl)]thiophene and 0.235 parts by mass of 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine were mixed, 6.7 parts by mass of dry tetrahydrofuran were added, and stirred for 15 minutes. Subsequently, 0.195 parts by mass of isopropylmagnesium chloride was added dropwise at a rate of 2s / drop under ice bath conditions, and the reaction was carried out at room temperature in the dark for 30 minutes to obtain formatted monomer A. Under nitrogen protection and ice bath conditions, 0. To 777 parts by mass of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 0.195 parts by mass of isopropyl magnesium chloride was added dropwise at 2s / drop, and the mixture was reacted at room temperature in the dark for 30 minutes to obtain a formatted monomer B; under nitrogen protection, 0.0098 parts by mass of 1,3-bis(diphenylphosphinopropane) nickel dichloride and 2.25 parts by mass of tetrahydrofuran were mixed and stirred for 30 minutes, and then the formatted monomer A was added dropwise at 2s / drop under ice bath conditions. After the addition was complete, the ice bath was removed and stirred at room temperature. The reaction was stirred for 3 hours, and the formatted monomer B was added, and the reaction was continued to stir at room temperature for 3 hours. After the reaction was completed, it was quenched with 1M hydrochloric acid under ice bath conditions, and then the extract was diluted with deionized water until the aqueous phase was almost colorless. The organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure on a rotary evaporator. Then, 10 parts by mass of chloroform was added to dissolve it and added to n-hexane in batches for precipitation. The mixture was centrifuged 3 times at 5800 rpm for 10 minutes each time to remove oligomers with small molecular weight and unreacted monomers. , pour off the upper layer of poor solvent, vacuum dry in a vacuum oven at 45°C for 8h, then mix with 20.2 parts by mass of 48% hydrobromic acid and 20.2 parts by mass of acetic anhydride under nitrogen protection, then heat to 100°C, react for 23h, extract with deionized water and ether three times to take the organic phase, wash with saturated sodium bicarbonate solution until the organic phase is neutral, collect the organic phase, add anhydrous magnesium sulfate to dry, filter, remove the solvent under reduced pressure on a rotary evaporator, and vacuum dry in a vacuum oven at 45°C for 8h to obtain amphiphilic polythiophene.
[0072] (Example 3)
[0073] A method for preparing a low-defect, few-layer graphene aqueous conductive slurry comprises the following steps:
[0074] (1) Weigh the raw material components according to the following mass parts: 3 parts by mass of low-defect few-layer graphene, 100 parts by mass of ultrapure water, and 0.8 parts by mass of conductive additive;
[0075] (2) Under argon protection, the low-defect few-layer graphene weighed in step (1) was dispersed in anhydrous dimethyl sulfoxide (DMSO) 6 times its mass and ultrasonically dispersed for 65 minutes, and then a conductive additive was added and ultrasonic dispersion was continued for 35 minutes. Then, the temperature was first raised to 62°C, cooled to room temperature, and stirred at 800 rpm for 25 hours. Then, sodium hydride was added three times with an interval of 25 minutes between each two times, and the amount added each time was 0.48 parts by mass. Then, the temperature was raised to 80°C, stirred and refluxed for 6.5 hours, and then 20 parts by mass of ethyl acetate was added to quench, and then 30 parts by mass of ethyl acetate was added. Then, the mixture was filtered, washed with dichloromethane and ether 4 times respectively, and then dried in a vacuum oven at 50°C to constant weight to obtain a low-defect few-layer graphene composite conductive material;
[0076] (3) The low-defect few-layer graphene composite conductive material obtained in step (2) is mixed with the ultrapure water weighed in step (1), and ultrasonically dispersed for 65 minutes to obtain a low-defect few-layer graphene aqueous conductive slurry.
[0077] The preparation steps of the low-defect few-layer graphene are as follows:
[0078] A1. Graphite powder and chromium trioxide were mixed in a mass ratio of 1:9. 8 parts by mass of 38% hydrochloric acid were then added. The mixture was stirred at 1400 rpm under sealed conditions for 130 minutes. The mixture was then filtered and washed repeatedly with deionized water and acetone until the filtrate reached a neutral pH. The mixture was then vacuum-dried at 60°C to a constant weight to obtain room-temperature intercalated graphite powder.
[0079] A2. 0.2 parts by weight of room temperature intercalated graphite powder was immersed in 42 parts by weight of a 30% hydrogen peroxide solution. After reacting for 25 hours, the mixture was filtered and then repeatedly filtered and washed with deionized water and acetone until the filtrate had a neutral pH. The filtrate was then vacuum dried at 60°C to a constant weight to obtain a graphene precursor.
[0080] A3. Dissolve 0.025 parts by mass of 2',3'-dideoxyadenosine 5'-triphosphate sodium salt in 20 parts by mass of deionized water by stirring. Then, add 0.02 parts by mass of a graphene precursor. Ultrasonic exfoliation is performed at 100 W for 65 minutes at 15°C. The mixture after ultrasonic exfoliation is centrifuged at 5000 rpm for 35 minutes, and the supernatant is collected, filtered, and dried to obtain low-defect, oligolayer graphene.
[0081] 78% of the low-defect few-layer graphene has a thickness of less than 1.5 nm, and 72% of the low-defect few-layer graphene has a sheet diameter of 1 to 6 μm.
[0082] The ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.16.
[0083] The preparation method of the amphiphilic polythiophene is as follows:
[0084] Under nitrogen protection, 0.53 parts by mass of 3-[10-(4-methylphenyl ether)decyl)]thiophene and 0.24 parts by mass of 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine were mixed, 7 parts by mass of dry tetrahydrofuran were added, and the mixture was stirred for 20 minutes. Subsequently, 0.196 parts by mass of isopropylmagnesium chloride was added dropwise at a rate of 3s / drop under ice bath conditions, and the mixture was reacted at room temperature in the dark for 35 minutes to obtain a formatted monomer A. Under nitrogen protection and ice bath conditions, 0.778 parts by mass of methylphenyl ether was added dropwise at a rate of 3s / dropwise to obtain a monomer A. To 2 parts of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 0.196 parts by mass of isopropyl magnesium chloride was added dropwise at a rate of 3s / drop, and the mixture was allowed to react at room temperature in the dark for 35 minutes to obtain the formatted monomer B. Under nitrogen protection, 0.0099 parts by mass of 1,3-bis(diphenylphosphinopropane) nickel dichloride and 2.25 parts by mass of tetrahydrofuran were mixed and stirred for 35 minutes, and then the formatted monomer A was added dropwise at a rate of 3s / drop in an ice bath. After the addition was complete, the ice bath was removed and the mixture was stirred at room temperature for 3 minutes. 5h, add the formatted monomer B, continue to stir and react at room temperature for 3.5h, quench with 1M hydrochloric acid under ice bath conditions after the reaction, then use deionized water and extract the product until the aqueous phase is almost colorless, collect the organic phase, add anhydrous magnesium sulfate to dry, filter, and remove the solvent under reduced pressure on a rotary evaporator, then add 10 parts by mass of chloroform to dissolve and add it to n-hexane in batches for precipitation, centrifuge 3 times at 5800 rpm, each centrifugation for 10 minutes to remove small molecular weight oligomers and unreacted monomers, and discard. The upper layer of poor solvent was vacuum dried in a vacuum oven at 45°C for 8.5h, then mixed with 20.3 parts by mass of 48% hydrobromic acid and 20.3 parts by mass of acetic anhydride under nitrogen protection, then heated to 101°C, reacted for 25h, extracted four times with deionized water and ether to obtain an organic phase, washed with saturated sodium bicarbonate solution until the organic phase was neutral, collected the organic phase, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure in a rotary evaporator. The phase was vacuum dried in a vacuum oven at 45°C for 8.5h to obtain amphiphilic polythiophene.
[0085] (Comparative Example 1)
[0086] The difference between Comparative Example 1 and Example 2 is that the aqueous phase stripping solution of Comparative Example 1 adopts an aqueous solution mixed with 0.020 parts by mass of sodium deoxycholate and 20 parts by mass of ultrapure water, and the remaining steps and components are the same as Example 2; 78% of the low-defect few-layer graphene has a thickness of less than 2 nm, and 70% of the low-defect few-layer graphene has a sheet diameter of 1~6 μm; the ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.21.
[0087] (Comparative Example 2)
[0088] The difference between Comparative Example 2 and Example 2 is that the conductive additive in Comparative Example 2 is prepared by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene and 3-[10-(4-methylphenyl ether)decyl)]thiophene and then treating with hydrogen bromide and anhydrous acetic anhydride, and the remaining steps and components are the same as those in Example 2; 78% of the low-defect few-layer graphene has a thickness of less than 1.3 nm, and 75% of the low-defect few-layer graphene has a sheet diameter of 1~6 μm; the ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.16.
[0089] (Comparative Example 3)
[0090] The difference between Comparative Example 3 and Example 2 is that the conductive additive in Comparative Example 3 is prepared by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene and 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine and then treating with hydrogen bromide and anhydrous acetic anhydride, and the remaining steps and components are the same as those in Example 2; 78% of the low-defect few-layer graphene has a thickness of less than 1.4 nm, and 73% of the low-defect few-layer graphene has a sheet diameter of 1~6 μm; the ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.17.
[0091] (Comparative Example 4)
[0092] The difference between Comparative Example 4 and Example 2 is that the conductive additive in Comparative Example 4 is prepared by polymerization of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 3-[10-(4-methylphenyl ether)decyl)]thiophene, and 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine, and the remaining steps and components are the same as those in Example 2. 78% of the low-defect few-layer graphene has a thickness of less than 1.1 nm, and 75% of the low-defect few-layer graphene has a sheet diameter of 1~6 μm; the ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.16.
[0093] (Comparative Example 5)
[0094] The difference between Comparative Example 5 and Example 2 is that the low-defect few-layer graphene aqueous conductive slurry of Comparative Example 5 directly mixes and disperses the low-defect few-layer graphene, conductive additives, and ultrapure water weighed in step (1), and the remaining steps and components are the same as those in Example 2; 78% of the low-defect few-layer graphene has a thickness of less than 1.2 nm, and 74% of the low-defect few-layer graphene has a sheet diameter of 1 to 6 μm; and the ratio of the D peak to the G peak of the low-defect few-layer graphene is 0.16.
[0095] (Effect example)
[0096] Viscosity: The rotational viscometer method described in DB13 / T 5026.1-2019 was used for testing.
[0097] Determination of the resistivity of the slurry electrode: The four-probe method described in DB13 / T 5026.3-2019 is used for detection.
[0098] Table 1 below shows the performance test results of the low-defect, few-layer graphene aqueous conductive pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 5:
[0099] Table 1
[0100] Electrode resistivity (Ω*cm) Viscosity (mPa*s) Viscosity after standing for 2 months (mPa*s) Example 1 21.8 1134 1270 Example 2 20.6 1109 1208 Example 3 21.2 1125 1237 Comparative Example 1 24.7 1142 1324 Comparative Example 2 21.6 1132 1290 Comparative Example 3 24.1 1128 1274 Comparative Example 4 23.7 1126 1272 Comparative Example 5 28.3 1619 3076
[0101] It can be seen from Table 1 and the graphene test data of the embodiments and comparative examples that the low-defect few-layer graphene prepared in Examples 1 to 3 has few defects and good dispersibility in the prepared low-defect few-layer graphene aqueous conductive slurry. The dispersibility remains good after standing for two months; and the prepared low-defect few-layer graphene aqueous conductive slurry has high conductivity.
[0102] The difference between Comparative Example 1 and Example 2 is that the aqueous phase stripping solution of Comparative Example 1 adopts an aqueous solution of 0.020 parts by mass of sodium deoxycholate and 20 parts by mass of ultrapure water, instead of the aqueous solution of 5'-adenine nucleotide salt in Example 2. Compared with Example 2, the low-defect few-layer graphene aqueous conductive slurry prepared in Example 2 has higher conductivity and better dispersibility, and the dispersibility can still be maintained at a high level after standing for 2 months, and the dispersion stability is better.
[0103] The difference between Comparative Example 2 and Example 2 is that the conductive additive in Comparative Example 2 is prepared by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene and 3-[10-(4-methylphenyl ether)decyl)]thiophene and then treating with hydrogen bromide and anhydrous acetic anhydride. Compared with Comparative Example 2, Example 2 further adds 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine. The obtained low-defect few-layer graphene aqueous conductive slurry has good dispersibility, and the dispersibility can still be maintained at a high level after standing for 2 months, and the dispersion stability is good.
[0104] The difference between Comparative Example 3 and Example 2 is that the conductive additive in Comparative Example 3 is prepared by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene and 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine and then treating with hydrogen bromide and anhydrous acetic anhydride. Compared with Comparative Example 2, Example 2 further adds 3-[10-(4-methylphenyl ether)decyl)]thiophene. The obtained low-defect few-layer graphene aqueous conductive slurry has good dispersibility, and the dispersibility can still maintain a high level after standing for 2 months. The dispersion stability is good, and the obtained low-defect few-layer graphene aqueous conductive slurry has high conductivity.
[0105] The difference between Comparative Example 4 and Example 2 is that the conductive additive in Comparative Example 4 is prepared by polymerization of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 3-[10-(4-methylphenyl ether)decyl)]thiophene, and 2,4,6-tris(5-bromothiophene-2-yl)-1,3,5-triazine. The low-defect few-layer graphene aqueous conductive slurry prepared in Example 2 has good dispersibility, and the dispersibility can still be maintained at a high level after standing for 2 months. The dispersion stability is good, and the conductivity of the prepared low-defect few-layer graphene aqueous conductive slurry is high.
[0106] The difference between Comparative Example 5 and Example 2 is that the low-defect few-layer graphene aqueous conductive paste of Comparative Example 5 directly disperses the low-defect few-layer graphene, conductive additives, and ultrapure water weighed in step (1), rather than pre-mixing the low-defect few-layer graphene and conductive additives as in Example 2. The low-defect few-layer graphene aqueous conductive paste prepared in Example 2 has better dispersibility, and the dispersibility can still maintain a high level after standing for 2 months. The conductivity of the prepared low-defect few-layer graphene aqueous conductive paste is higher.
[0107] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A low-defect few-layer graphene aqueous conductive slurry, characterized in that: Calculated by weight, the raw material components include 1 to 3 parts by weight of low-defect few-layer graphene, 100 parts by weight of ultrapure water, and 0.8 to 1.2 parts by weight of a conductive additive.
2. The low-defect few-layer graphene aqueous conductive paste according to claim 1, characterized in that: The low-defect few-layer graphene is obtained by first intercalating graphite powder at room temperature, then chemically expanding it, and then exfoliating it using an aqueous solution of 2',3'-dideoxyadenosine 5'-triphosphate.
3. The low-defect few-layer graphene aqueous conductive paste according to claim 1, characterized in that: The conductive additive is amphiphilic polythiophene.
4. The low-defect few-layer graphene aqueous conductive paste according to claim 3, characterized in that: The amphiphilic polythiophene is obtained by polymerizing 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 3-[10-(4-methylphenyl ether)decyl)]thiophene and 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine as polymerization monomers and then treating the obtained monomers with hydrogen bromide and anhydrous acetic anhydride.
5. A method for preparing the low-defect few-layer graphene aqueous conductive slurry according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: (1) Weigh each raw material component according to its mass fraction; (2) Under argon protection, the low-defect few-layer graphene weighed in step (1) is dispersed in anhydrous dimethyl sulfoxide 4 to 6 times its mass and ultrasonically dispersed for 55 to 65 minutes, and then a conductive additive is added, and ultrasonic dispersion is continued for 25 to 35 minutes. Then, the temperature is first raised to 58 to 62°C, and after cooling to room temperature, it is stirred at 600 to 800 rpm for 23 to 25 hours, and sodium hydride is added three times, with an interval of 15 to 25 minutes between each two times, and the amount added each time is 0.32 to 0.48 parts by mass. Then, the temperature is raised to 70 to 80°C, stirred and refluxed for 5.5 to 6.5 hours, and then 18 to 20 parts by mass of ethyl acetate is added to quench, and then 27 to 30 parts by mass of ethyl acetate is added. Then, the mixture is filtered, washed with dichloromethane and ether for 2 to 4 times respectively, and then dried in a vacuum oven at 50°C to constant weight to obtain a low-defect few-layer graphene composite conductive material; (3) The low-defect few-layer graphene composite conductive material obtained in step (2) is mixed with the ultrapure water weighed in step (1), and ultrasonically dispersed for 55 to 65 minutes to obtain a low-defect few-layer graphene aqueous conductive slurry.
6. The method for preparing the low-defect few-layer graphene aqueous conductive paste according to claim 5, characterized in that: The preparation steps of the low-defect few-layer graphene are as follows: A1. Graphite powder and chromium trioxide were mixed in a mass ratio of 1:8-9. 6-8 parts by mass of 36-38% hydrochloric acid were then added. The mixture was stirred at 1000-1400 rpm for 110-130 minutes under sealed conditions. The filtrate was then filtered and washed repeatedly with deionized water and acetone until the pH was neutral. The filtrate was then vacuum-dried at 60°C to constant weight to obtain room-temperature intercalated graphite powder. A2. Immerse 0.2 parts by weight of room-temperature intercalated graphite powder in 38-42 parts by weight of a 30% hydrogen peroxide solution. Allow to react for 23-25 hours, then filter and wash repeatedly with deionized water and acetone until the filtrate reaches a neutral pH. Dried under vacuum at 60°C to constant weight to obtain a graphene precursor. A3. Dissolve 0.015–0.025 parts by weight of 2',3'-dideoxyadenosine 5'-triphosphate sodium salt in 20 parts by weight of deionized water. Add 0.02 parts by weight of a graphene precursor and perform ultrasonic exfoliation at 100 W for 55–65 minutes at 10–15°C. Centrifuge the mixture at 5000 rpm for 25–35 minutes, collect the supernatant, filter, and dry to obtain low-defect, oligolayer graphene.
7. The method for preparing the low-defect few-layer graphene aqueous conductive paste according to claim 6, characterized in that: 78% of the low-defect few-layer graphene has a thickness of less than 2 nm, and 74% of the low-defect few-layer graphene has a sheet diameter of 1 to 6 μm.
8. The method for preparing the low-defect few-layer graphene aqueous conductive paste according to claim 6, characterized in that: The ratio of the D peak to the G peak of the low-defect few-layer graphene is not higher than 0.
2.
9. The method for preparing the low-defect few-layer graphene aqueous conductive paste according to claim 5, characterized in that: The preparation method of the amphiphilic polythiophene is as follows: Under nitrogen protection, 0.51-0.53 parts by mass of 3-[10-(4-methylphenyl ether)decyl)]thiophene and 0.23-0.24 parts by mass of 2,4,6-tris(5-bromothiophen-2-yl)-1,3,5-triazine were mixed, 6.3-7 parts by mass of dry tetrahydrofuran were added, and the mixture was stirred for 10-20 minutes. Subsequently, 0.194-0.196 parts by mass of isopropylmagnesium chloride was added dropwise at a rate of 1-3 seconds per drop under ice bath conditions, and the mixture was reacted at room temperature in the dark for 25-35 minutes to obtain a formatted monomer A. Under nitrogen protection and ice bath conditions, 0. To 776~0.778 parts by mass of 2,5-dibromo-3-triethylene glycol monomethyl ether thiophene, 0.194~0.196 parts by mass of isopropyl magnesium chloride was added dropwise at a rate of 1~3s / drop, and the mixture was allowed to react at room temperature in the dark for 25~35min to obtain the formatted monomer B; under nitrogen protection, 0.0097~0.0099 parts by mass of 1,3-bis(diphenylphosphinopropane) nickel dichloride and 2.25 parts by mass of tetrahydrofuran were mixed and stirred for 25~35min, and then the formatted monomer A was added dropwise at a rate of 1~3s / drop in an ice bath. After the addition was complete, the ice bath was removed. The reaction was stirred at room temperature for 2.5 to 3.5 hours, the formatted monomer B was added, and the reaction was continued to be stirred at room temperature for 2.5 to 3.5 hours. After the reaction was completed, it was quenched with 1M hydrochloric acid under ice bath conditions, and then deionized water and the extracted product were used until the aqueous phase was almost colorless. The organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure on a rotary evaporator. Then 10 parts by mass of chloroform was added to dissolve it and added to n-hexane in batches for precipitation. The mixture was centrifuged at 5800 rpm for 2 to 3 times, each time for 10 minutes, to remove oligomers with small molecular weight and unreacted monomers, and the upper unreacted phase was discarded. The mixture was dried in a vacuum oven at 45°C for 7.5-8.5h, and then mixed with 20.1-20.3 parts by mass of 48% hydrobromic acid and 20.1-20.3 parts by mass of acetic anhydride under nitrogen protection, and then heated to 99-101°C. After reacting for 20-25h, the organic phase was extracted 2-4 times with deionized water and ether, and washed with saturated sodium bicarbonate solution until the organic phase was neutral. The organic phase was collected, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure in a rotary evaporator. The amphiphilic polythiophene was obtained by vacuum drying at 45°C in a vacuum oven for 7.5-8.5h.
10. A use of the low-defect few-layer graphene aqueous conductive slurry according to any one of claims 1 to 4, characterized in that: The low-defect few-layer graphene aqueous conductive slurry is used in the preparation of batteries, conductive coatings, conductive inks, flexible sensors, and electric heating films.
Citation Information
Patent Citations
Method for preparing high-quality graphene
CN102408107A
Graphene / polythiophene composite weatherable electroconductive corrosion-resistant size
CN107955512A
Preparation method of graphene conductive paste
CN110071290A
Amphipathic conjugated polymer and production method and application thereof
CN110229314A
Method for preparing double-layer graphene
CN113247889A